Analysis and validation of a quasi-dynamic model for a solar collector field with flat plate collectors and parabolic trough collectors in series for district heating. (1st January 2018) - Tian, Zhiyong; Perers, Bengt; Furbo, Simon; Fan, Jianhua
Abstract: A quasi-dynamic TRNSYS simulation model for a solar collector field with flat plate collectors and parabolic trough collectors in series was described and validated. A simplified method was implemented in TRNSYS in order to carry out long-term energy production analyses of the whole solar heating plant. The advantages of the model include faster computation with fewer resources, flexibility of different collector types in solar heating plant configuration and satisfactory accuracy in both dynamic and long-term analyses. In situ measurements were taken from a pilot solar heating plant with 5960 m 2 flat plate collectors and 4039 m 2 parabolic trough collectors in series in Taars, Denmark from Sep.2015 to Aug.2016. The simulated thermal performances of both the parabolic trough collector field and the flat plate collector field have a good agreement with the measured performances. The thermal performance of the hybrid solar district heating plant is also presented. The measured and simulated results show that the integration of parabolic trough collectors in solar district heating plants can guarantee that the system produces hot water with relatively constant outlet temperature. The daily energy output of the parabolic trough collector field can be more than 5 kWh/m 2, while the daily energy output of the flat plate collector field is less than 5 kWh/m 2 under Danish climate conditions. The simplified and validated TRNSYS model can be a useful tool to simulate and optimize thermal performance of solar heating plants with both flat plate and parabolic trough collectors. Highlights: A quasi-dynamic model for the hybrid solar collector field has been validated. The model is validated with annual measured data of a hybrid solar collector field. Dynamic and long-term thermal performances of the hybrid solar field were shown. The proposed model addresses dynamic conditions with low computational resources.